A rare case of pediatric enteroplueural fistula, which presented as lung abscess - James, Saji; Agarwal, Prakash; Vinoth, P N; Subramanian, Balagopal; Rakesh, P (Indian Journal of Child Health, 2015)
We report a case of a 14-year-old male patient referred to us as a case of right-sided lung abscess. The patient was treated for the enteric perforation elsewhere, following which he developed productive cough, which progressively worsened. The preoperative diagnosis of entero-pleural fistula was made with the help of thoraco abdominal computed tomography scan after 4 months of antitubercular and antibiotic treatment. Enteric perforation leading to entero-pleural fistula is very rare. The patient did well after laparotomy and completeexcision of the fistula.